Patient safety attitudes in the next generation of healthcare providers. A review of the literature. (20th October 2021) - Tocco Tussardi, I; Benoni, R; Moretti, F; Tardivo, S; Poli, A; Wu, AW; Rimondini, M; Busch, IM
Abstract: Background: A comprehensive understanding of the attitudes towards patient safety of the new generation of healthcare workers is fundamental not only for ensuring safe, high-quality care in the present but also for creating a safer healthcare setting in the future. This study aimed to systematically review the literature on patient safety attitudes of health professional students, new graduates, newly registered health professionals, and resident trainees, and to examine potential differences in this population with respect to year of study, specialty, and gender. Methods: We searched four databases (i.e., PubMed, Web of Science, Scopus, and PsycInfo) up to 20/02/2020 and screened also additional sources, including weekly, automatic e-mailed search alerts up to 18/10/2020. Two reviewers independently performed all methodological steps (i.e., search, study selection, quality appraisal, data extraction and formal narrative synthesis), including a third reviewer in case of disagreement. Results: We identified 6606 records, assessed 188 full-texts, and included 31 articles. Across studies, healthcare students and young professionals reported more positive patient safety attitudes in certain domains (e.g., teamwork climate, error inevitability, received patient safety training) but showed more negative attitudes in other areas (e.g., management support, safety climate, disclosure responsibility). Women and persons with more years of study and training demonstrated more positive attitudes towards patient safety. Conclusions: Healthcare students should receive early curricular education in patient safety to build a solid foundation for the development of a strong and healthy safety culture. Understanding the differences in attitudes between aspiring healthcare providers from different areas is important to tailor teaching and training to the specific needs of certain populations. Key messages: According to the reviewed literature, young healthcare students and professionals' attitudes towards patient safety differed across domains. Institutions should increase education and training on patient safety for aspiring healthcare professionals, tailor them to the specific needs of this population, and monitor attitudes over time.